An approximate approach on the buckling analysis of a composite lattice cylindrical panel. (1st November 2020) - Kim, Yongha; Park, Jungsun
Abstract : This paper defines the modified effective stiffness considering the direction-dependent mechanical properties to an intersection of ribs and mode shape function of a composite lattice cylindrical panel. It subsequently presents an approximate method based on the continuous model of conducting a buckling analysis of the composite lattice cylindrical panel with various boundary conditions under uniform compression. This method considers the coupled buckling mode as well as the global and local buckling modes. We verify the validity of the present method by comparing the results of the finite element analysis. In addition, parametric and sensitivity analyses are performed to investigate the effects of the design parameters on the buckling characteristics based on the present method. The results allow a database to be obtained on the buckling characteristics by design parameters. Finally, the present method is applied to optimizing a composite lattice cylindrical panel for wing box design to minimize the mass. Consequently, it is concluded that the present method is very suitable for an optimization involved in the buckling analysis of composite lattice cylindrical panels due to their relative simplicity and computational efficiency.